1976
DOI: 10.1111/j.1365-2621.1976.tb01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muscle Type on Residual Nitrite in Cured Meat

Abstract: When a cured meat model system was made from white muscle it contained less residual nitrite than if it were made from a red muscle; this effect is due to the lower pH of white muscle. If the pH of red and white muscle is similar then the slightly lower residual nitrite in products made from red muscle probably is due to the greater content of myoglobin in red muscle. INTIiODUCTION CONSIDERABLEATTENTION has been focused recently on the use of nitrite in foods. The reason for this is twofold. First, a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Different authors have highlighted the conversion of nitrite into nitrate in meat products in amounts larger than those observed in this experiment (10,25,37). However, in the absence of reducing agents the level of conversion was considerably lower (11).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Different authors have highlighted the conversion of nitrite into nitrate in meat products in amounts larger than those observed in this experiment (10,25,37). However, in the absence of reducing agents the level of conversion was considerably lower (11).…”
Section: Resultsmentioning
confidence: 90%
“…Because the nitrite added to meat products interacts with several components of the complex biological systems, it is known to become rapidly depleted depending on factors such as initial nitrite concentration, presence of reductants, acidity, product composition, and processing and storage conditions (9,10). In spite of the desirable benefits of nitrite, there has been controversy over its use as a meat-curing agent, partly because of its potential to react with amines and amides to form carcinogens and partly because of its contribution as a source of nitrite in human nutrition (11). Recently, it has been highlighted that residual nitrite found in cured meat products has been substantially reduced (as much as 80%), thanks to, among other factors, changes in the manufacturing process (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…, reported that as pH decreases, the reactivity of nitrite increases due to more favorable nitritemyoglobin interactions resulting in lower residual nitrite concentrations. This is in agreement with Lee, Cassens and Fennema (1976) who demonstrated that a lower pH directly resulted in lower concentrations of residual nitrite.…”
Section: Residual Nitritesupporting
confidence: 93%
“…The presence or addition of curing accelerators including ascorbate and erythorbate, serve as reducing agents which in turn accelerate the curing reaction resulting in lower levels of residual nitrite (Lee and Shimakoa 1984). Lee, Cassens and Fennema (1976) (Sebranek 1979). Addition of non-meat ingredients including alkaline phosphates and the addition of poultry meat in the formulation has also been found to alter overall product pH in turn effecting residual nitrite levels (Prusa and Kregel 1985).…”
Section: Residual Nitritementioning
confidence: 99%